Shift In The Paradigm Of Islamic Education: Evaluation Of The 2013 Curriculum In The Era Of The Merdeka Curriculum - Nofrizal, Edi; Nofrizal, Nofrizal; Mitra, Fitria; Faisal, Muhammad; Lahmi, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This study aims to evaluate the paradigm shift in Islamic Religious Education (PAI) related to the implementation of the 2013 Curriculum and the Merdeka Curriculum. This shift is analyzed using the Systematic Literature Review (SLR) method to identify similarities, differences, and their impacts on learning and character development of students. The SLR research protocol used refers to the PRISMA guidelines, with data collected from credible academic sources such as Google Scholar, Scopus, and SINTA. The findings show that the Merdeka Curriculum offers greater flexibility for teachers in selecting teaching methods and materials, and places more emphasis on strengthening the values of religious moderation. In contrast, the 2013 Curriculum is more structured, focusing on competency-based learning and a scientific approach. The implications of this paradigm shift include changes in the teacher's role to that of a facilitator, the integration of technology in learning, and the adjustment of competency-based evaluation methods. This study also identifies opportunities such as strengthening religious moderation values and the development of a digital-based curriculum, as well as implementation challenges including teacher preparedness and differing perceptions in the application of the curriculum. Based on these findings, the article provides recommendations for teacher training, the provision of supporting facilities, and government policies to offer flexibility in the implementation of PAI across educational units